1
$\begingroup$

I came across the following proof in my textbook that was used as a end of chapter review. How can I prove the following algebraically?

$$\left( \begin{array}{c} 2n \\ 2\ \end{array} \right) = 2 \left( \begin{array}{c} n \\ 2\ \end{array} \right) + n^2$$

using $\left( \begin{array}{c} n \\ 2\ \end{array} \right) = \dfrac{n(n-1)}{2}$?

$$\left( \begin{array}{c} 2n \\ 2\ \end{array} \right) = \frac{2n(2n-1)}{2} = 2n(n-1) = 2 \frac{n(n-1)}{2} + n^2 = 2\left( \begin{array}{c} n \\ 2\ \end{array} \right) + n^2 $$

Is this proof correct? if not how do I fix it?

$\endgroup$
  • 2
    $\begingroup$ $2n(n-1)$ should be $n(2n-1)$ $\endgroup$ – Joe Feb 6 '18 at 23:18
  • $\begingroup$ besides that error its correct? $\endgroup$ – user123 Feb 6 '18 at 23:19
  • 1
    $\begingroup$ Yes, but I think you need more exposition to show $n(2n-1) = 2 \frac{n(n-1)}{2} + n^2$ $\endgroup$ – Joe Feb 6 '18 at 23:20
  • $\begingroup$ Duplicate MSE question $\endgroup$ – Somos Feb 7 '18 at 1:50
3
$\begingroup$

It is not correct, and it should go like this:

$$\binom{2n}{2}=\frac{2n(2n-1)}{2}=n(2n-1)=2n^2-n=n(n-1)+n^2=2\frac{n(n-1)}{2}+n^2=2\binom{n}{2}+n^2$$

It looks that your work starts well and ends well but there is a bit of a muddle in the middle.

$\endgroup$
  • $\begingroup$ thanks for clarifying this! $\endgroup$ – user123 Feb 6 '18 at 23:30
6
$\begingroup$

$$\binom{2n}{2} = \frac{2n(2n-1)}{2} = \frac{2n(n-1) + 2n^2}{2} = 2 \binom{n}{2} + n^2$$

$\endgroup$
  • $\begingroup$ thanks for your submission! $\endgroup$ – user123 Feb 6 '18 at 23:30
3
$\begingroup$

Since OP asks for an algebraic proof, I type this proof making use of number of roots of a degree two polynomials for fun.

Set $f(n) = \left( \begin{array}{c} 2n \\ 2\ \end{array} \right) - 2 \left( \begin{array}{c} n \\ 2\ \end{array} \right) - n^2 $. Since $\deg f \le 2$, $f$ has at most two distinct roots. \begin{align} f(2) &= \left( \begin{array}{c} 4 \\ 2\ \end{array} \right) - 2 \left( \begin{array}{c} 2 \\ 2\ \end{array} \right) - 4 = 6-2-4=0 \\ f(3) &= \left( \begin{array}{c} 6 \\ 2\ \end{array} \right) - 2 \left( \begin{array}{c} 3 \\ 2\ \end{array} \right) - 9 = 15-6-9=0 \\ f(4) &= \left( \begin{array}{c} 8 \\ 2\ \end{array} \right) - 2 \left( \begin{array}{c} 4 \\ 2\ \end{array} \right) - 16 = 28-12-16=0 \end{align}

Therefore, $f$ is identically zero. Hence $\left( \begin{array}{c} 2n \\ 2\ \end{array} \right) = 2 \left( \begin{array}{c} n \\ 2\ \end{array} \right) + n^2$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.